The advertisement call of Proceratophrys redacta (Anura, Odontophrynidae) - Simões, Cássio Rachid M. A.; de Pontes, Bruna Elizabeth Silva; Trevisan, Camila Costa; de Abreu, Rafael Oliveira; Juncá, Flora Acuña; Solé, Mirco; de Araújo, Carlos Barros; Napoli, Marcelo Felgueiras (Zootaxa, 2020)
The genus Proceratophrys Miranda-Ribeiro, 1920, frogs from the family Odontophrynidae Lynch, currently contains 41 nominal species with poorly resolved phylogenetic relationships (Frost 2019; Mângia et al. 2018). Molecular data from 15 and 18 Proceratophrys species support the monophyletic hypothesis of the genus (Teixeira-Jr et al. 2012; Dias et al. 2013; respectively) but do not fully resolve the phylogenetic relationship among the species. Currently, there are advertisement call parameters provided for 31 species of Proceratophrys in the literature (Ferreira et al. 2016; Andrade et al. 2018; Mângia et al. 2018; Nascimento et al. 2019). The Proceratophrys advertisement call is composed of pulsed notes, amplitude modulation, short to medium duration calls (0.05–4 s) and only one note in almost all species (see Nascimento et al. 2019 for details). Considering the importance of bioacoustics for taxonomy (Köhler et al. 2017), further descriptions of advertisement calls for the genus could also improve our understanding of the species’ relationships.